Research progress of UV/sulfite system on degradation of pollutants in water - SHEN Kaiyue; WEI Wenbo; ZHANG Xinhuan (Gongye shui chuli)
Advanced reduction processes(ARPs) based on UV/sulfite(UV/SO32-) have received increasing attention due to high degradation capacity for some refractory pollutants. This paper described the reaction mechanism of UV/sulfite processes, summarized the influencing factors of UV/sulfite process, introduced the application scenarios and improvement methods of UV/sulfite process, and looked forward to the future research and development direction of UV/sulfite processes. It was concluded that UV/sulfite process had excellent performance in the degradation of inorganic and organic pollutants. The hydrated electrons were the dominant active species in UV/sulfite degradation system. The UV light source, sulfite concentration, dissolved oxygen, pH and co-existing substances in the water were the main factors affecting the degradation effect of UV/sulfite process.